2004
DOI: 10.1149/1.1630595
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effect of AC-Treated, Mixed Self-Assembled Film of Phenylthiourea and 1-Dodecanethiol on Copper Corrosion

Abstract: A new method for preparing effective inhibition film on copper has been developed. Phenylthiourea was first adsorbed to a copper surface to form a self-assembled film. 1-Dodecanethiol was then self-assembled on the surface for subsequent modification. Finally, ac voltage was loaded on copper covered with the mixed film to further modify the film. After these procedures, an effective inhibition film was obtained as indicated by the low corrosion current density in polarization curves. High charge-transfer resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Organic compounds containing polar group including nitrogen, sulphur, and oxygen [3][4][5][6][7][8][9] have been reported to inhibit copper corrosion. The inhibitions of these organic compounds are usually attributed to their interactions with the copper surface via adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds containing polar group including nitrogen, sulphur, and oxygen [3][4][5][6][7][8][9] have been reported to inhibit copper corrosion. The inhibitions of these organic compounds are usually attributed to their interactions with the copper surface via adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds containing polar groups including nitrogen, sulfur, and oxygen (Gomma and Wahdan 1994, Zucchi, Trabanelli and Fonsati 1996, Kendig and Jeanjaquet 2002, Ma et al 2004, Christy et al 2004, Zhang, Gao, and Zhou 2004, Otmacic et al 2004, and Wang, Chen and Zhao 2004 and heterocyclic compounds with polar functional groups and conjugated double bonds (Al-Kharafi, 1988, Elmorsi and Hassanein 1999, Otmacic and Stupnisek-Lisac 2002, Dafali et al 2002, Scendo, Poddebniak and Malyszko 2003, Sherif 2011, and Sherif 2013 have been reported to be good corrosion inhibitors. The inhibiting action of these organic compounds is usually attributed to their interactions with the metal surface via their adsorption.…”
Section: Organic Inhibitorsmentioning
confidence: 99%
“…Inhibitors are chemicals that often work by adsorbing themselves on the metallic surface by forming a film (Noor, 2008;Ebenso et al, 2008;Oguzie, 2006). Organic compounds containing polar groups including nitrogen, sulfur, and oxygen (Otmacic et al, 2004;Ma et al, 2002;Wang et al, 2004;Kendig and Jeanjaquet, 2002;Ma et al, 2003), and heterocyclic compounds with polar functional groups and conjugated double bonds (Elmorsi and Hassanein, 1999;Al-Kharafi, 1988;Scendo et al, 2003) have been reported to inhibit copper corrosion. The inhibiting action of these organic compounds is usually attributed to their interactions with the copper surface via their adsorption.…”
Section: Introductionmentioning
confidence: 99%